Analysis of the temperature distribution in a space heated by a dynamic (fan) storage heater - Lysak, Oleg (Eastern-European Journal of Enterprise Technologies, 2017)
The experimental and research space heating system with a fan storage heater was introduced. The system contains a set of measurement tools, which allows studying the temperature distribution at several room points simultaneously. Temperature recording has begun since the heating season 2014–2015 and it is continued up to date. Temperature measurement error in the range of 10...25 °C accounts for 6.8...2.8 %, respectively. The greatest errors in studies are from temperature sensors and the controller-logger unit, which records temperature values. The regulation of the storage heater is performed using the values from two temperature sensors located in the same plane but at different heights. Depending on the temperature readings of the sensors, the storage heater fan was switched on and off. During the research, the temperature change at different heights of the space depending on the fan mode was studied. The study found that when a fan is on, this leads to the formation of overheating zone. This fact negatively affects the comfortable conditions for people inside that space and results in overspending of thermal energy stored by a storage heater. The study also showed that the lower the set room temperature, the lower the temperature gradient (along the height) and the duration of overheating periods. This fact creates favorable conditions for the construction of the algorithm for the storage heater automation system that would allow avoiding overheating.